2000
DOI: 10.1046/j.1365-2141.2000.02217.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of helper T‐cell precursor frequencies against non‐haemopoietic cells: comparison of co‐stimulation provided by anti‐CD28 antibody versus the cellular ligand B7‐1

Abstract: Helper T‐cell precursor frequency assays (HTLp‐assays) are commonly used in transplantation to examine the frequency of T cells reactive against donor or host alloantigens. In these assays, peripheral blood mononuclear cells (PBMCs) are most often used as stimulator cells. However, cells targeted after transplantation do not always belong to the haematopoietic lineage and may express different alloantigens, especially minor histocompatibility antigens (mHags). Non‐haematopoietic cells lack expression of the B7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…This promoted the induction of T-cell survival signals by bcl-xL. 21,22 All these results suggest that the inclusion of anti-CD28i to anti-CD3i activation may be of critical relevance for preserving the functionality of T cells during in vitro cell manipulations. 23 In addition to the in vitro studies, the infusion of T cells previously subjected to in vitro activation showed a reduced GVHD in allogeneic recipients, compared to reactions mediated by fresh T cells.…”
Section: Introductionmentioning
confidence: 94%
“…This promoted the induction of T-cell survival signals by bcl-xL. 21,22 All these results suggest that the inclusion of anti-CD28i to anti-CD3i activation may be of critical relevance for preserving the functionality of T cells during in vitro cell manipulations. 23 In addition to the in vitro studies, the infusion of T cells previously subjected to in vitro activation showed a reduced GVHD in allogeneic recipients, compared to reactions mediated by fresh T cells.…”
Section: Introductionmentioning
confidence: 94%